FLOUTING MAXIMS BY INDONESIAN PRESIDENTIAL CANDIDATES IN THE 2024 PRESIDENTIAL DEBATE - Imansyah, Ananda Adil; Maharani, Reriskha; Afkarina, Fika Sofiah; Sutrisno, Adi (Program Studi Bahasa Inggris, Universitas Panca Marga, 2024)
This research specifically examines the non-observance of conversational maxims in the third presidential debate on defense, geopolitics, and international relations. It observes that there are fewer instances where presidential candidates flout the Maxim of Quantity and the Maxim of Relevance compared to the Maxim of Manner. The analysis concludes that Grice’s Cooperative Principle, which emphasizes cooperation in communication, is often contravened by candidates. The findings suggest that presidential candidates are more likely to flout the Maxim of Quantity and the Maxim of Relevance to persuade the audience of their position’s validity, as these maxims relate to their reputation. This study provides insights into political communication during debates and how the public perceives candidates’ strategies. Additionally, the study identifies intentional breaches of conversational maxims by candidates to manipulate public opinion, which can be advantageous for them. This research highlights the variability of communication strategies depending on the audience and circumstances. It has significant implications for understanding the impact of political communication strategies on public opinion and election outcomes.